A novel framework for rural homestead land transfer under collective ownership in China. (November 2018) - Kong, Xuesong; Liu, Yaolin; Jiang, Ping; Tian, Yasi; Zou, Yafeng
Highlights: Identifying the advantages and disadvantages of the extant RHL transfer modes. A new framework for RHL transfer is established based on the separation of three rights and two values. A long-term mechanism to protect farmers' interests is built under collective membership. It increases the understanding of the relationships among farmers, collectives, and governments. Abstract: Rapid urbanization in China has triggered the mass migration of rural populations to cities, resulting in a shortage of urban land and inefficient use of rural homestead land (RHL). To address these issues, there is increasing interest in allowing for RHL transfer. Although several transfer modes have been implemented in pilot areas, the long-term protection of farmers' interests has been largely neglected. One-off transfer compensation and forced transfer often occur in practice, and there is no collective profit sharing. This paper explores the advantages and disadvantages of the extant transfer modes using comparative analysis. We propose a novel RHL transfer system under collective ownership, and three highly related key aspects add layers of protection: the separation of three sets of rights (ownership, tenure, and membership), the separation of land value from the value of accessory buildings and durable goods, and profit sharing among the collective members. The advantages of the proposal are summarized as follows: (1) it provides long-term protection for farmers' interests based on membership in the collective; (2) endows the collective with actual rights of self-governance and collective autonomy; and (3) decreases institutional costs and reform risks and improves land-use efficiency of RHL. The implications of the proposal regarding topics of concern are also discussed. This study offers a clear direction for RHL transfer and increases the understanding of the essence of the collective ownership of RHL and relationships among farmers, collectives, and governments during RHL transfer.